2016
DOI: 10.3310/hsdr04070
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the cost-effectiveness and clinical effectiveness of a new community in-reach rehabilitation service with the cost-effectiveness and clinical effectiveness of an established hospital-based rehabilitation service for older people: a pragmatic randomised controlled trial with microcost and qualitative analysis – the Community In-reach Rehabilitation And Care Transition (CIRACT) study

Abstract: (2016) Comparing the cost-effectiveness and clinical effectiveness of a new community in-reach rehabilitation service with the cost-effectiveness and clinical effectiveness of an established hospital-based rehabilitation service for older people: a pragmatic randomised controlled trial with microcost and qualitative analysis -the Community In-reach Rehabilitation And Care Transition (CIRACT) study. Health Services and Delivery Research, 4 (7). ISSN 2050-4357 Access from the University of Nottingham reposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The HOME intervention was assessed in a randomized control trial (RCT) involving 400 older patients with varied medical conditions treated in five acute Australian hospitals [28]. Consistent with other evidence-based interventions [30,31], no between-group differences were found between HOME compared to the in-hospital occupational therapy consultation on the main outcomes (independence in ADL, participation in life roles, and hospital and ED readmissions) in this trial [28].…”
Section: Introductionmentioning
confidence: 76%
“…The HOME intervention was assessed in a randomized control trial (RCT) involving 400 older patients with varied medical conditions treated in five acute Australian hospitals [28]. Consistent with other evidence-based interventions [30,31], no between-group differences were found between HOME compared to the in-hospital occupational therapy consultation on the main outcomes (independence in ADL, participation in life roles, and hospital and ED readmissions) in this trial [28].…”
Section: Introductionmentioning
confidence: 76%
“…Manageable transitions exhibit features consistent with the goals of the GEM model of care (Ellis et al , 2011) and components of successful care transition interventions (Sahota et al , 2016). Numerous studies have reported the importance of active engagement of patients and the need to make adjustments to care plans based on patient experience (Coleman et al , 2004; Walker et al , 2015; Allen et al , 2016; Cheek et al , 2006) As reported elsewhere (Allen et al , 2016; Baillie et al , 2014; Giosa et al , 2014; Byrne et al , 2011) carers in this study had a critical role in optimising care transitions by seeking out information, negotiating with providers and promoting self-management.…”
Section: Discussionmentioning
confidence: 94%
“…Interventions to improve older people’s care transition experiences and reduce readmission rates and length of stay have shown mixed results. A recent synthesis of international systematic reviews identified the essential components of successful interventions as: more intensive rehabilitation, working more closely with older people and carers, and a dedicated transition provider to advocate for and facilitate care co-ordination and outreach to patients following discharge from hospital (Sahota et al , 2016). Despite this, an intervention utilising these approaches showed no benefit in reducing hospital readmissions or length of stay (Sahota et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A number of different initiatives have been trialled to reduce length of hospital stay and readmission rates; including tailored structured discharge plans, which may have a small effect, but overall cost benefits are still inconclusive (Shepperd et al ., 2010). A randomised controlled trial comparing a community in-reach rehabilitation and care transition with the ‘usual’ discharge to rehabilitation service on length of hospital stay and readmission rates found no difference between the two approaches (Sahota et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%